2016
DOI: 10.1007/s10926-016-9650-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Cultural Influences, and Coping with Musculoskeletal Pain at Work: The Experience of Malaysian Female Office Workers

Abstract: Purpose Workers with musculoskeletal pain (MSP) often continue to work despite their condition. Understanding the factors that enable them to remain at work provides insights into the development of appropriate workplace accommodations. This qualitative study aims to explore the strategies utilised by female Malaysian office workers with MSP to maintain productive employment. Methods A qualitative approach using thematic analysis was used. Individual semi-structured interviews were conducted with 13 female Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…This provided a glimpse to the authors that all the nursing staff participated in the study, irrespective of their ergonomic training (only 57% had training) followed their own coping mechanisms to manage their work related stress. Findings by Maakipet et al (2017) [30] in their study also illustrated that the participants developed their own coping strategies to assist them to remain at work, but most focused on individually initiated adaptations or peer support, rather than systemic changes to work systems or practices.The most prominently followed strategies by the nurses in the study were noticed as making use of a different body part to adopt the burden and taking a pause to change the posture during their work. Even though all the nurses are not exposed to ergonomic training, almost all of them adopted the natural coping mechanism.…”
Section: Coping Strategiesmentioning
confidence: 79%
“…This provided a glimpse to the authors that all the nursing staff participated in the study, irrespective of their ergonomic training (only 57% had training) followed their own coping mechanisms to manage their work related stress. Findings by Maakipet et al (2017) [30] in their study also illustrated that the participants developed their own coping strategies to assist them to remain at work, but most focused on individually initiated adaptations or peer support, rather than systemic changes to work systems or practices.The most prominently followed strategies by the nurses in the study were noticed as making use of a different body part to adopt the burden and taking a pause to change the posture during their work. Even though all the nurses are not exposed to ergonomic training, almost all of them adopted the natural coping mechanism.…”
Section: Coping Strategiesmentioning
confidence: 79%
“…Maakip et al [24] found age as significant predictor of musculoskeletal discomfort among Malaysian officer workers but not age. Likewise, in terms of mixed findings, Seppala [25] and Demure e al [26] found only gender explained variance in musculoskeletal discomforts but not age.…”
Section: Age and Gender Effectsmentioning
confidence: 96%
“…Bazı kültürlerde bireyler ağrıları konusunda daha açık olurken, diğerleri ağrılarını ve duygularını gizler. Malezya'da hiyerarşik, yetki ayrımına dayalı bir yapı olması nedeniyle Malay çalışan kadınların batılı meslektaşlarına göre yaşadıklarını daha az ifade eder durumda oldukları ve ifadelerinde daha çekingen oldukları gözlenmiştir [45]. Kültürlerin toplumsal cinsiyete yüklediği anlamların içeriği bakımından kadın ve erkeklerin sağlık arama davranışlarını değiştirdiği görülmektedir.…”
Section: Farklı Kültürlerde Toplumsal Cinsiyet Ve Ağrıunclassified